A genetic system for biasing the sex ratio in mice. (1st July 2019) - Yosef, Ido; Edry‐Botzer, Liat; Globus, Rea; Shlomovitz, Inbar; Munitz, Ariel; Gerlic, Motti; Qimron, Udi
Abstract: Biasing the sex ratio of populations of different organisms, including plants, insects, crustacean, and fish, has been demonstrated by genetic and non‐genetic approaches. However, biasing the sex ratio of mammalian populations has not been demonstrated genetically. Here, we provide a first proof of concept for such a genetic system in mammals by crossing two genetically engineered mouse lines. The maternal line encodes a functional Cas9 protein on an autosomal chromosome, whereas the paternal line encodes guide RNAs on the Y chromosome targeting vital mouse genes. After fertilization, the presence of both the Y‐encoded guide RNAs from the paternal sperm and the Cas9 protein from the maternal egg targets the vital genes in males. We show that these genes are specifically targeted in males and that this breeding consequently self‐destructs solely males. Our results pave the way for a genetic system that allows biased sex production of livestock. Synopsis: Biasing the sex ratio by genetic and non‐genetic approaches has been demonstrated for diverse organisms except higher vertebrates. This study provides proof of concept for a genetic system in mammals that allows biased sex production. Two transgenic lines encoding Cas9 or Y‐chromosome‐encoded gRNAs are crossed. Lethality occurs when Cas9 is guided to target essential genes. As gRNAs are Y‐chromosome‐encoded only male offspring is affected. Abstract : Biasing the sex ratio by genetic and non‐genetic approaches has been demonstrated for diverse organisms except higher vertebrates. This study provides proof of concept for a genetic system in mammals that allows biased sex production.